Individualism during Crises - Bian, Bo; Li, Jingjing; Xu, Ting; Foutz, Natasha Z. (The Review of Economics and Statistics, 2022)
Individualism has long been linked to economic growth. Using the COVID-19 pandemic, we show that such a culture can hamper the economy's response to crises, a period with heightened coordination frictions. Exploiting variation in U.S. counties' frontier experience, we show that more individualistic counties engage less in social distancing and charitable transfers and are less willing to receive COVID-19 vaccines. The effect of individualism is stronger where social distancing has higher externality and holds at the individual level when we exploit migrants for identification. Our results suggest that individualism can exacerbate collective action problems during economic downturns.